HUBUNGAN KEPUASAN KERJA DAN KINERJA PEGAWAI KOPERASI SAWIT KARYA BHAKTI DESA MAHATO - Betty Leindarita; Yuritanto Yuritanto; Armansyah Armansyah (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the relationship between work and employee performance of the Karya Bhakti Palm Oil Cooperative in Mahato Village. The population and sample in this study were all employees of the Karya Bhakti Cooperative in Mahato Village, which operates 30 employees. Sampling technique is using saturated sampling technique. The data collection tool uses a google form questionnaire. The tests carried out in the study were in the form of data normality tests and correlation tests. It can be obtained from the results of data processing shows that it has a positive and significant relationship to the Employee Performance of the Karya Bhakti Oil Palm Cooperative in Mahato Village